2021
DOI: 10.1007/s11695-021-05417-7
|View full text |Cite
|
Sign up to set email alerts
|

Interventions and Operations after Bariatric Surgery in a Health Plan Research Network Cohort from the PCORnet, the National Patient-Centered Clinical Research Network

Abstract: Purpose Obesity is a highly prevalent condition with severe clinical burden. Bariatric procedures are an important and expanding treatment option. This study compared short-(30-day composite adverse events) and long-term (intervention/operation, endoscopy, hospitalization, and mortality up to 5 years) safety outcomes associated with three bariatric surgical procedures. Materials and Methods This observational cohort study replicated an electronic health re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 28 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…Weiner's study consisted of patients who underwent BS from 2002 to 2008, in which 12.3% of study participants AGB, 38.3% had laparoscopic gastric bypass, and 35.4% had open gastric bypass. However, 46.8% of patients in the current study underwent the SG procedure, which has shown to be safer with less risk of hospitalization in both the short‐ and long‐term than AGB and bypass 11,13 …”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…Weiner's study consisted of patients who underwent BS from 2002 to 2008, in which 12.3% of study participants AGB, 38.3% had laparoscopic gastric bypass, and 35.4% had open gastric bypass. However, 46.8% of patients in the current study underwent the SG procedure, which has shown to be safer with less risk of hospitalization in both the short‐ and long‐term than AGB and bypass 11,13 …”
Section: Discussionmentioning
confidence: 77%
“…which has shown to be safer with less risk of hospitalization in both the short-and long-term than AGB and bypass. 11,13 A study by Smith et al, that looked at bariatric surgeries between 2000 and 2011 using Veterans' Affairs (VA) health care system data to study 10-year downstream healthcare cost, saw increases in total health care expenditures in the first 2 years after BS and then observed similar costs to the non-surgery group in the next 8 years. 18 In contrast, this study saw increased Year 1 cost followed by decreased Year 2 to Year 10 cost in the surgery group.…”
Section: Ses Analysis Results In Surgical Cohortmentioning
confidence: 99%
See 3 more Smart Citations